THE PUBLIC RELATIONS TEAM'S STRATEGY IN IMPROVING ACHIEVEMENT AND REPUTATION AT MTSN 1 PASER - Riduan, Riduan; Zamroni, Zamroni; Baharun, Hasan (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This research aims to analyze the strategies implemented by the public relations team at MTsN 1 Paser in improving student achievement, both in academic and non-academic fields. In the era of globalization and advances in information technology, effective communication is one of the key factors in supporting the achievement of an educational institution. The research approach used was qualitative with a case study method, which involved in-depth interviews with members of the public relations team, school principals, as well as students and parents as key informants. The collected data was then analyzed using thematic analysis techniques to identify communication patterns and strategies used by the public relations team. The research results show that the public relations strategy implemented by MTsN 1 Paser includes strengthening internal communication through regular meetings with stakeholders, effective social media management, and involving parents in various school activities. Through these strategies, students' academic and non-academic achievements have increased significantly, although there are still several challenges related to limited budgets and human resources. It is hoped that this research can provide insight for education managers in optimizing the role of public relations as part of efforts to improve the quality of education in Indonesia